2021
DOI: 10.1073/pnas.2103198118
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic electrically driven soft valve for control of soft hydraulic actuators

Abstract: Significance Soft actuators have advantages over traditional rigid robots in various applications due to their robustness, low mechanical stiffness, and low weight. Thus far, conventional rigid valves are the most common approach to control hydraulic soft actuators. Although soft valves have been designed in various forms, they have not achieved the pressure or flow rate conditions as required by many existing hydraulic actuators. In this paper, we introduce an electrically driven soft valve using dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 52 publications
1
22
0
2
Order By: Relevance
“…The maximum energy and power output densities of PHDE are superior to those of natural muscles and DEAs developed in recent years (Fig. 2D) (2,24,(27)(28)(29)(30)(31), which enable lightweight, energy-dense actuation systems. A PHDE film was demonstrated to toss an aluminum ball, which is 20 times as heavy as itself, to 12.1 cm high (Fig.…”
mentioning
confidence: 99%
“…The maximum energy and power output densities of PHDE are superior to those of natural muscles and DEAs developed in recent years (Fig. 2D) (2,24,(27)(28)(29)(30)(31), which enable lightweight, energy-dense actuation systems. A PHDE film was demonstrated to toss an aluminum ball, which is 20 times as heavy as itself, to 12.1 cm high (Fig.…”
mentioning
confidence: 99%
“…We constructed the DEAs using a low-viscoelasticity and high–dielectric strength silicone material, Elastosil P7670 (Wacker Chemical). From a previous study ( 45 ), a multilayer rolled DEA made from P7670 silicone exhibited a large quality factor of six and a high breakdown field of 66 V ÎŒm −1 under AC excitation. Owing to the material properties of silicone, these DEAs reached an estimated energy density of 4.9 J kg −1 and had sufficient bandwidth (600 Hz or higher) for the pump goals ( 45 ).…”
Section: Resultsmentioning
confidence: 82%
“…S1). A DEA structure contained two rolled DEAs combined in parallel, with each DEA consisting of sequentially layered carbon nanotube electrodes and elastomer sheets ( 44 , 45 ). Two or more DEAs were aligned in parallel and mounted to the top plate of the mechanical frame, with their free ends in contact with the channel via indenters.…”
Section: Resultsmentioning
confidence: 99%
“…To define the target ranges for output and input pressures, we surveyed soft actuators and microfluidic circuits. The ranges of values noted here and in the remainder of this section will be used to define the ranges of our targets for the metrics mentioned; despite quoted data for these measurements being sparse in the literature, we found that a common command input for soft actuators is 103.4 kPa [22][23][24][25][26][27][28] while microfluidic output signals vary from 3.4 to 34.5 kPa due to the large resistances of the narrow channels which cause a large pressure drop limiting the output pressure at flow rates relevant to typical soft fluidic actuators. [29] Therefore, a gain range that guarantees that all microfluidic output signal magnitudes can be amplified to drive the largest soft robotic loads is 3-30.…”
Section: Performance Metricsmentioning
confidence: 99%